3D bioprinting of skin constructs for toxicology testing - Ng, Wei Long (2018)
The high discrepancies between adverse effects of chemicals in animal and human have led to the development of alternative in-vitro human tissue models to improve the reliability and accuracy of toxicology testing. 3D bioprinting technology has emerged as an advanced platform that facilitates simultaneous and highly-specific patterning of multiple types of cells and biomaterials, which is lacking in conventional tissue engineering approaches. The goal of this review is to highlight the achievements in skin bioprinting and present the future outlook on standardization of in-vitro human tissue models for toxicology testing.